The clinical-immunological analysis of a specific and combined immunotherapy of patients with cervical cancer - D. K. Kenbayeva; A. F. Lazarev (ABV-press, 2014)
Research objective is the comparative assessment of efficiency of two various ways of an immunotherapy of patients with cervical cancer. 57 patients with cervical cancer, the III stages, distributed on 3 groups - combined radiotherapy, a combination of a radiotherapy and specific immunotherapy, and also a radiotherapy, specific and adaptive immunotherapy are surveyed. Clinical efficiency of treatment was estimated by means of primary tumor regression and 3-year survival rate. The scheme of combined immunotherapy was shown to possess the most clinical efficiency. Positive dynamics of cell immunity indicators was accompanied to clinical efficiency of treatment.